2010
DOI: 10.1007/s10267-009-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu2+, Mn2+ and aromatic compounds on the production of laccase isoforms by Coprinus comatus

Abstract: Six different extracellular laccase isoforms were identified in submerged cultures of the commercially important edible mushroom, Coprinus comatus. Although laccase activity (*55 IU/L) was readily detectable in unsupplemented control cultures containing 1.6 lM Cu 2? after 22-day incubation, mean enzyme levels (*150-185 IU/L) were 2.7-3.4-fold higher in cultures supplemented with 0.5-3.0 mM Cu 2? . Laccase production was also stimulated by Mn supplementation over the range 0.05-0.8 mM Mn 2? , and the peak value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
17
0
2
Order By: Relevance
“…Although Song and van Griensven 21 determined a high correlation among the polyphenols and polysaccharides of different medicinal mushroom extracts (R=0.82), our study revealed no connection between these compounds ( Table 2). According to Lu and Ding, 25 naturally derived antioxidant compounds of Coprinus comatus include total phenols, flavonoids, tocopherols, and polysaccharides. The results of our study revealed no correlation between the content of polysaccharides and antioxidant capacity of mushroom blends.…”
Section: Discussionmentioning
confidence: 99%
“…Although Song and van Griensven 21 determined a high correlation among the polyphenols and polysaccharides of different medicinal mushroom extracts (R=0.82), our study revealed no connection between these compounds ( Table 2). According to Lu and Ding, 25 naturally derived antioxidant compounds of Coprinus comatus include total phenols, flavonoids, tocopherols, and polysaccharides. The results of our study revealed no correlation between the content of polysaccharides and antioxidant capacity of mushroom blends.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported the effect of the inductors, copper and manganese, in improving laccase activity depending on the substrate, organism, crop, and the concentrations of these metals (Giardina et al 2000, Baldrian et al 2005, Stajić et al 2006, Lu & Ding 2010. For example, Baldrian et al (2005) reported that average laccase activity increases 79 % with Cu addition in cultures of P. ostreatus on wheat straw.…”
Section: Discussionmentioning
confidence: 99%
“…Trong khi ở một số loài nấm khác, thí dụ như hoạt tính laccase tăng 180,5% ở P. ostreatus Em-1 khi bổ sung 10 mM ion Mn 2+ [12], tăng 4,5 lần trong môi trường có nồng độ Mn 2+ 0,8 mM đối với Coprinus comatus [10].…”
Section: ảNh Hưởng Của Mn 2+unclassified